Enhancing Public Speaking Skills through Role-Playing: A Case Study at Riyadlotul Athfal Al-Ghozali Islamic Boarding School - Muttaqin, Muttaqin; Husni, Muhammad; Acetylena, Sita (AL-ISHLAH: Jurnal Pendidikan, 2026)
Public speaking is an essential communication skill for students in Islamic boarding schools, particularly for supporting religious learning, public preaching, and social participation. However, many students still experience anxiety, limited confidence, and difficulty organizing ideas when speaking before an audience. This study examines the use of role-playing as a holistic learning method to support students’ public speaking development at Riyadlotul Athfal Al-Ghozali Islamic Boarding School. This study employed a qualitative case study design involving 18 students and 3 teachers selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation during public speaking and pesantren learning activities. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing, with source and technique triangulation applied to enhance credibility. The findings indicate that role-playing provided students with repeated opportunities to practice realistic communication situations. Students showed improvement in confidence, speech organization, audience engagement, eye contact, vocal variation, and body language. Teachers also observed greater student participation, spontaneity, and willingness to speak in front of peers. Role-playing supports public speaking development by integrating cognitive, affective, and psychomotor dimensions of learning. In the pesantren context, this method is relevant because scenarios can be aligned with Islamic values and daily communication practices, such as religious speeches and group discussions. The study suggests that role-playing can be systematically integrated into pesantren-based public speaking instruction, although broader studies are needed to examine its application across different Islamic educational settings.